PENGARUH CRM DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS PELANGGAN PADA ONLINE SHOPE JOSHSTORE BATAM - sari, Ratna; Raymond, Raymond (SCIENTIA JOURNAL, 2021)
Online shop contend in selling items depending on the situation today with their individual attributes to draw in however many clients as could be allowed to purchase their items and feel fulfillment with the items they get. This investigation plans to dissect the impact of CRM and consumer loyalty on client faithfulness at Online Shope Joshstore Batam. The sort of exploration utilized is quantitative examination with a populace of 130 individuals. The instrument used to gather information is a poll. The testing method taken is a soaked example. The information is prepared utilizing SPSS rendition 25 with the aftereffects of the examination realized that t check > t table is 6.018 > 1.656 with an importance worth of 0.000 <0.05, t tally Consumer Satisfaction is known > t The table is 7.522 > 1.656 with a meaning of 0.000 < 0.05. Furthermore, there is CRM and Customer Satisfaction together have a positive and huge impact on client devotion. It is demonstrated by the aftereffects of the F (concurrent) test with a worth of (F tally) 127.341 > 2.67 (F table) with a huge worth at 0.000 < 0.05. Furthermore, the R Square worth is 0.667